Numerical analysis of the effect of opposite baffles on the heat transfer enhancement of non-newtonian Nano fluid through a backward facing step - Kourosh Javaherdeh; Mehdi Moslemi; Motahare Mahmoodnezhad (Big Data and Computing Visions)
In this paper, the effect of opposite baffles on the flow field and the increase of forced heat transfer of non-Newtonian nanofluid flow in a laminar regime in a backward-facing step are investigated numerically. The finite volume method is used to solve the governing equations of flow and temperature. Besides, the impact of geometric parameters such as horizontal distance between baffles to the edge of the stairs and its numbers, like Reynolds number, nanoparticle volume fraction, and the non-Newtonian fluid behavior on the flow field and heat transfer have been examined. Results demonstrate that using non-Newtonian fluid instead of Newtonian fluid enhances heat transfer and reattachment length. Raising the Reynolds number and the nanofluid volume fraction causes the mean Nusselt numbers and the Performance Evaluation Index to increase. The outcomes indicate that using a pair of opposite baffles must be more beneficial than the other number of baffles.